2015
DOI: 10.1039/c4ra16375c
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive spectroscopic investigation of α-(2-naphthyl)-N-methylnitrone: a computational study on photochemical nitrone–oxaziridine conversion and thermal E–Z isomerization processes

Abstract: This comprehensive spectroscopic analysis of a-(2-naphthyl)-N-methylnitrone has proposed its photochemical oxaziridine formation and thermal E-Z isomerization mechanisms. The activation energy for the conversion of the unstable non-planar E isomer to the stable planar Z-isomer is found to be 23.7 kcal mol À1 at the CASSCF/6-31G* level of calculation. A transition state with a negative frequency of 350 cm À1 is likely to be responsible for this process. Both CASSCF and ONIOM-based studies have revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Interestingly, both transformation barriers become much smaller at the excited state, and the barrier of TTVTT(OEt) (0.45 eV) is lower than that of TTVTT (0.67 eV), which indicates the S⋯O noncovalent interactions turned to destabilize the planar conformation at excited state. Also, the low barrier from trans‐ to cis‐ TTVTT(OEt) resulted in the easy mutual conversion at room temperature . The calculated PESs of TTVTT(OEt) solid at S 0 and S 1 also demonstrate that the transformation barriers become extremely large at S 0 and S 1 (Figure S11, Supporting Information), suggesting the isomerization is significantly difficult in solid state.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, both transformation barriers become much smaller at the excited state, and the barrier of TTVTT(OEt) (0.45 eV) is lower than that of TTVTT (0.67 eV), which indicates the S⋯O noncovalent interactions turned to destabilize the planar conformation at excited state. Also, the low barrier from trans‐ to cis‐ TTVTT(OEt) resulted in the easy mutual conversion at room temperature . The calculated PESs of TTVTT(OEt) solid at S 0 and S 1 also demonstrate that the transformation barriers become extremely large at S 0 and S 1 (Figure S11, Supporting Information), suggesting the isomerization is significantly difficult in solid state.…”
Section: Resultsmentioning
confidence: 98%
“…In our present calculations, we have used an active space consisting of 4 active electrons in 4 active orbitals (4,4) for studying the possibility of oxaziridine formation from the trifluomethylsubstituted nitrone. This choice of CAS space in our present work has been done based on the prior experience of successful tracking of the nitrone-oxaziridine photoconversion path of our previously studied retinyl nitrone, their model compounds and naphthyl nitrone systems; [7][8][9] the choice made in those cases were based on the chemical intuition looking at their reported experimental photochemical results. 5,6 In all these cases, the CASSCF studies had confirmed that the oxaziridine ground state species is formed through the lowest-energy conical intersection geometry which involves a terminal CNO twist, and this process was found to be perfectly captured by use of a proper (4,4) active space.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The chemopreventive N-methyl retinylnitrone 6 w a sf o u n dt oc o n v e r t slowly to stable oxaziridine under the exposure to room light. Recently our group [7][8][9] has also identified oxaziridine as the primary photoproduct of these types of nitrones from computational analysis. In fact, it is now well-known from experimental studies that N-alkyl group on nitrones stabilizes the oxaziridine while the N-aryl or electron-withdrawing groups (EWG) on nitrogen have an opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical reactions of nitrones have been thoroughly investigated by our group in the last few years . Various categories of acyclic and cyclic nitrones have been analyzed through quantum mechanical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical reactions of nitrones have been thoroughly investigated by our group in the last few years. [1][2][3][4][5][6] Various categories of acyclic and cyclic nitrones have been analyzed through quantum mechanical studies. Experimental results reported for these nitrones were clearly justified by these abinitio-based calculations.…”
Section: Introductionmentioning
confidence: 99%